2014
DOI: 10.1210/jc.2013-2684
|View full text |Cite
|
Sign up to set email alerts
|

ATLANTIC-DIP: Excessive Gestational Weight Gain and Pregnancy Outcomes in Women With Gestational or Pregestational Diabetes Mellitus

Abstract: We show that in the already high-risk settings of both GDM and PGDM, excessive GWG confers an additive risk for LGA birth weight, macrosomia, and gestational hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
106
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 29 publications
18
106
1
2
Order By: Relevance
“…Similarly, the weekly gestational weight gain between in the first and second halves of pregnancy was calculated as the difference between the weight measured at a midpregnancy routine visit (21 [19][20][21][22][23][24] weeks) and the self-reported prepregnancy weight and the difference between the weight measured at 21 weeks and the last weight measured in pregnancy (36 [34][35][36][37][38][39] weeks), respectively, divided by the number of weeks of observation with days precision.…”
Section: Prepregnancy Bmi and Gestational Weight Gainmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the weekly gestational weight gain between in the first and second halves of pregnancy was calculated as the difference between the weight measured at a midpregnancy routine visit (21 [19][20][21][22][23][24] weeks) and the self-reported prepregnancy weight and the difference between the weight measured at 21 weeks and the last weight measured in pregnancy (36 [34][35][36][37][38][39] weeks), respectively, divided by the number of weeks of observation with days precision.…”
Section: Prepregnancy Bmi and Gestational Weight Gainmentioning
confidence: 99%
“…In 2009, the Institute of Medicine (IOM) suggested the following recommendations for BMI-appropriate gestational weight gain: 12.5-18.0 kg for underweight, 11.5-16.0 kg for normal weight, 7.0-11.5 kg for overweight, and 5.0-9.0 kg for obese women (19). Whether these IOM recommendations are applicable in women with pregestational type 1 or type 2 diabetes still remains unclear (20)(21)(22). Existing studies on the topic mainly include overweight and obese women with gestational diabetes mellitus or type 2 diabetes and show that excessive gestational weight gain increases the risk of large-for-gestationalage infants and macrosomia (20)(21)(22)(23) and is associated with higher rates of cesarean section (21,22), neonatal morbidity (21,23), and gestational hypertension (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ATLANTIC-DIP study recently reported that excessive weight gain was associated with greater odds of developing GH in 543 women with GDM (OR 1.72 (95%CI 1.04, 2.85)) [7]. The association of gestational weight gain and PE is not universally reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest a relationship of PE frequency with ethnicity and in particular that Maori women may be at higher risk of PE [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%